Pengaruh Motivasi, Pengetahuan Akuntansi dan Relogiusitas terhadap Kualitas Lulusan Program Studi Akuntansi Syariah - Azza Nikmatuttisaroh (Jurnal Akuntansi dan Keuangan Islam, 2014)
Along with the development of economy and business, the competitiveness of it isincreasing. Increasing competitiveness requires educational institutions tocontinuously improve the quality of graduates.This study aims to determine the effectof motivation, knowledge of accounting, and religiosity on the quality of graduatesinSTEI SEBI Islamic Accounting courses. The sources of data in this study is theprimary data obtained directly from responses to questionnaires of IslamicAccounting graduates tudy program. Data collection techniques is performed by thesurvey. Data obtained using a questionnaire administration to graduates of IslamicAccounting courses. The sample selection is done by using random sampling method.The data is analysed by the test of descriptive statistics, test of validity and reliability,the assumptions of classical test (test of normality, multicollinearity, andheteroskedastisity), as well as multiple linear hypothesis test. The results of theresearch shows that the partial motivation test is not significantly by the quality ofgraduates, while knowledge of accounting is significantly influence on religiosity at95% confidence level. Simultaneously, motivation, knowledge of accounting, andreligiosity significantly influence the quality of graduates. R Square value in thisstudy is 0.373, which means that 37.3% changes in the level of quality of graduatescan be explained by the variables of motivation, knowledge of accounting, andreligiosity, while the rest is influenced by other variables that are not observed in thisstudy. The results of this study are expected to contribute towards improving thequality of graduates of Islamic Accounting courses as a consideration in determiningthe necessary policies.